ANALYSIS OF THE IMPACT OF EDUCATION AND TRAINING PROGRAMS ON IMPROVING EMPLOYEE PERFORMANCE - Aprilla Intan Fatima; Oktarizka Reviandani (stiatabalong.ac.id, 2025)
Competency development is crucial in managing State Civil Apparatus (ASN), but issues such as unmet training hours, unimplemented competency matrices, and an imbalance of competencies in government agencies have hindered ASN quality and professionalism. This study examines the impact of education and training programs on employee performance. Using a qualitative descriptive research method, the study involved six LLDikti Region IV employees who participated in Goods and Services Procurement Training. Data were collected through observation, interviews, and documentation, and analyzed using the Kirkpatrick evaluation model. The findings indicate that the training program effectively enhanced employee competence, performance, motivation, and alignment with organizational goals, though improvements are needed in certain areas. The study highlights the importance of training in improving employee performance by developing technical, managerial, and socio-cultural competencies. To optimize productivity and goal achievement, organizations should design training programs aligned with work needs, supported by ongoing evaluation, strategic investment, and strengthened monitoring. Keywords: Education and Training, Employee Performance, Kirkpatrick